A Proposed Instructional Model for Using Mobile Learning in Universities of Jordan - Aldeeri, Tahani Ahmed; Al-Wraikat, Mansour Ahmed (Journal of Innovation and Research in Primary Education, 2024)
This study aimed to develop a proposed instructional model for the use of mobile learning in jordanian universities. The study followed the qualitative curriculum as required by the nature of the study, the number of study members for the qualitative aspect (19) faculty members for the academic year (2023-2024), the interview questions were built to explore the facts about the standard levels to be available in the instructional model. The results of the study revealed the stages of the proposed instructional model, and showed that the educational design obtained the highest percentage of standard levels to be available in the proposed instructional model. The study also concluded with a number of recommendations, the most important of which are: studying the effectiveness of the proposed instructional model using mobile learning among jordanian university students, and conducting a study similar to the current study of public and private schools.